Linguistic and identity quests in the multipolar African French-speaking environment. The case of Tanzania in East Africa - (:unkn) unknown (My University, 2021)
This thesis, fruit of a field survey, offers a comprehensive analysis on the link between identity and teaching/learning a foreign language. The exploration of the Francophonie lying in East Africa for sixty years through qualitative research led in Tanzania between 2013 and 2016 offers an overview of the linguistic policy engaged since 1970 between France and different countries of the region (Burundi, Kenya, Democratic Republic of Congo, Rwanda, Uganda). It highlights a political and diplomatic complexity as well as quartered identities in a French-speaking world inherited from the colonial time facing strategic innovations in an English-speaking environment. Politically, French language and its attributes are closely linked to the way France positions itself in the world. In the early 1970’s geopolitics was marked by a worldwide European decolonial process and the Cold War confronting countries in two camps. Since 2000, the emergence of China especially in Africa pushes France to reposition itself in the world on one hand by rocking this francocentric Francophonie, and on the other hand by leaving French speakers facing multiple readjustments in a national redefinition process. The epistemological framework offering phenomelogical and philosophical perspectives, opens the issue of identity affirmation in a didactic process of foreign language teaching fundamental to the understanding of discursive strategies of policies and analyses their evolvement over time. This perspective invites us thinking the new term of F(f)rancophonie embracing both an individual and an institutional dimension.
Keywords: African Research